2003
DOI: 10.1002/aic.690491012
|View full text |Cite
|
Sign up to set email alerts
|

Generalized least‐squares parameter estimation from multiequation implicit models

Abstract: Maximum likelihood fit of nonlinear, implicit, multiple-response models to data containing normally distributed random errors can be carried out by a combination of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…For batch equilibrium, nonconvergence of gradient method is due to local minima, flat zone of the error function or infinite loop phenomena 5. Extrapolation of these conclusions to inverse modelling of reactive transport lets expect many convergence problems for gradient like methods as assumed by Marshall 6. Even if the Monte‐Carlo methods are more time‐consuming, they are indeed more robust than the gradient‐like methods because they do not use the slope of the objective function.…”
Section: Introductionmentioning
confidence: 99%
“…For batch equilibrium, nonconvergence of gradient method is due to local minima, flat zone of the error function or infinite loop phenomena 5. Extrapolation of these conclusions to inverse modelling of reactive transport lets expect many convergence problems for gradient like methods as assumed by Marshall 6. Even if the Monte‐Carlo methods are more time‐consuming, they are indeed more robust than the gradient‐like methods because they do not use the slope of the objective function.…”
Section: Introductionmentioning
confidence: 99%
“…The Gauss-Newton generalized nonlinear least-square algorithm, first described by Britt and Luecke (1973), was employed for parameter estimation. The Gauss-Newton algorithm, which uses exact derivatives, and has been proven to converge in relatively few iterations and provide more accurate estimates of the asymptotic standard errors and covariance, is widely applied to a variety of engineering/scientific studies (Cooley, 1992;Demetracopoulos, 1994;Elmoursi and Gfrerer, 1994;Li et al, 2004;Marshall, 2003). The L 0 value of 322 m 3 /ton for LFG and 167 m 3 /ton for methane was determined, in comparison with Pelt et al (1998) andEnvironment Canada (2001) who have indicated L 0 of 340 m 3 /ton for LFG and 170 m 3 /ton for methane.…”
Section: Landfill Gas Generation Ratesmentioning
confidence: 43%
“…Monte Carlo (MC) simulation is a wide-ranging method to compute statistical characteristics of an output function utilizing a large number of iterations for its random variables. MC simulation has been successfully used for parameter estimation by many researchers, including Zhang and Guay (2002);Marshall, (2003); Aggarwal and Carrayrou, (2006).…”
Section: Monte Carlo Simulation Sampling and Genetic Algorithmmentioning
confidence: 99%